Oxidation‐Resistant Silver Nanostructures for Ultrastable Plasmonic Applications. (18th February 2013) - Sachan, R.; Ramos, V.; Malasi, A.; Yadavali, S.; Bartley, B.; Garcia, H.; Duscher, G.; Kalyanaraman, R.
<x xml:space="preserve">Abstract</x> Reduced degradation (oxidation) of silver nanoparticles (NPs) is achieved by contacting Ag with immiscible Co NPs. The relative decay of the plasmon peak (plot) shows that pure Ag NPs (blue dashed curve) decay by 25% in ca 20 days, whereas AgCo NPs last about 10 times longer, requiring nearly five months for a similar decay (red solid curve). The TEM images for both Ag and AgCo were taken after 50 days of storage under ambient conditions. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>